Pendidikan Progresif: Telaah Konsep Dalton Plan Helen Parkhurst - Syahid, Mar (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Education is an important aspect in human life. Because of the urgency of education, ideas about education that are relevant to current conditions continue to emerge. This aims to create education that is capable of forming people who have superior qualities and are useful for social life in the future. One of the educational streams that also contributes to the world of contemporary education is Progressivism education. This progressive education flow is a reaction to the traditional education system which is experiencing stagnation. Then, one of the well-known figures in Progressivism is Helen Parkhurst, an American educator who is famous for the concept of the Dalton Plan or The Dalton Laboratory Plan. This research aims to examine the concept of the Dalton Plan from Parkhurst using documentation study or literature study methods. Thus, this research is more about explaining the concepts, principles, objectives and steps of the Dalton Plan system contained in the book Education on The Dalton Plan (1922).